2022
DOI: 10.1002/adma.202206762
|View full text |Cite
|
Sign up to set email alerts
|

Stable Anode‐Free All‐Solid‐State Lithium Battery through Tuned Metal Wetting on the Copper Current Collector

Abstract: A stable anode‐free all‐solid‐state battery (AF‐ASSB) with sulfide‐based solid‐electrolyte (SE) (argyrodite Li6PS5Cl) is achieved by tuning wetting of lithium metal on “empty” copper current‐collector. Lithiophilic 1 µm Li2Te is synthesized by exposing the collector to tellurium vapor, followed by in situ Li activation during the first charge. The Li2Te significantly reduces the electrodeposition/electrodissolution overpotentials and improves Coulombic efficiency (CE). During continuous electrodeposition exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 128 publications
2
28
0
Order By: Relevance
“…This implies the synergistic effect of the combination of a chlorine-rich Li-argyrodite and a stable interlayer for AFASSBs. As a result, it achieved a steady-state cycling CE of 95% without any external pressure, which is comparable with reported values (84–92% CE under no pressure, 32 99% CE under 13 MPa, 41 99.8% under 30 MPa 31 ).…”
Section: Resultssupporting
confidence: 89%
“…This implies the synergistic effect of the combination of a chlorine-rich Li-argyrodite and a stable interlayer for AFASSBs. As a result, it achieved a steady-state cycling CE of 95% without any external pressure, which is comparable with reported values (84–92% CE under no pressure, 32 99% CE under 13 MPa, 41 99.8% under 30 MPa 31 ).…”
Section: Resultssupporting
confidence: 89%
“…No characteristic peaks of elemental Te were detected, indicating complete reaction of Te with the CF. [82] Figure S6, Supporting Information, displays transmission electron microscopy (TEM) analysis obtained from an electron transparent portion of a Cu 2 Te platelet. Figure S6a,b, Supporting Information, shows bright field images of the specimen, while Figure S6c, Supporting Information, provides a high-resolution TEM (HRTEM) image with an inset showing the associated selected area electron diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Interfacial materials, including Li alloys and others, have previously been investigated in anode-free and Li-excess SSBs to improve cycling. [36][37][38][39][40] Silver-carbon composite layers can facilitate uniform cyclic Li deposition/stripping. 12 Telluride layers have also been shown to promote uniform growth.…”
Section: Introductionmentioning
confidence: 99%
“…12 Telluride layers have also been shown to promote uniform growth. 38 Lithium-magnesium alloy interfaces can enhance diffusion and diminish voiding. 41 While these studies have shown improved cell performance, there is a lack of knowledge of the mechanistic influence of interfacial layers on the evolution of Li in anode-free SSBs.…”
Section: Introductionmentioning
confidence: 99%